2017
DOI: 10.1007/s00228-017-2260-0
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-induced neutropenia as a prognostic factor in patients with metastatic pancreatic cancer treated with gemcitabine

Abstract: Neutropenia during chemotherapy was associated with increased survival of patients with metastatic pancreatic cancer. Monitoring of CIN could be used to predict treatment responsiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…Our data were generally consistent with a previous report that showed that patients with severe neutropenia after treatment with gemcitabine-containing chemotherapy for advanced pancreatic cancer had significantly longer OS than those without it [ 19 ]. The survival effect of gemcitabine monotherapy for metastatic pancreatic cancer is better for patients with grade 3 neutropenia than those with lower grades of neutropenia [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data were generally consistent with a previous report that showed that patients with severe neutropenia after treatment with gemcitabine-containing chemotherapy for advanced pancreatic cancer had significantly longer OS than those without it [ 19 ]. The survival effect of gemcitabine monotherapy for metastatic pancreatic cancer is better for patients with grade 3 neutropenia than those with lower grades of neutropenia [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with advanced pancreatic cancer who received gemcitabine alone or in combination with other anticancer drugs, the median OS is significantly longer in patients with early onset of neutropenia than in those without neutropenia [ 19 ]. Comparison of the effect of gemcitabine monotherapy on survival among metastatic pancreatic patients with grade 3 neutropenia, those with grade 1–2 neutropenia and those without neutropenia also shows that the median survival time is prolonged with increasing grade of neutropenia [ 20 ]. Therefore, the incidence neutropenia may have different effects on the survival period, depending on the cancer type and chemotherapy regimen.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, chemoresistance is often observed, which greatly reduces the efficacy of chemotherapy (8). Gemcitabine (GEM), which is a first-line drug for the treatment of pancreatic cancer, has been reported to improve the therapeutic efficacy and patient quality of life compared with traditional chemotherapeutic agents (9). However, with the emergence of GEM resistance, the treatment efficacy of GEM in pancreatic cancer is declining (10).…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports suggest that adjuvant chemotherapy following curative surgery significantly contributes to prolong the overall patient survival time after surgery to remove the pancreatic cancer . Gemcitabine (GEM) is the first‐line drug currently available for treating pancreatic cancer in clinics . GEM is intracellularly phosphorylated by deoxycytidine kinase to GEM 5′‐diphosphate and GEM 5′‐triphosphate, which are incorporated into DNA, leading to apoptosis .…”
Section: Introductionmentioning
confidence: 99%